Forest Management in the Interface: Generating Income from Interface Forests - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS, 2008)
FOR174, a 6-page illustrated fact sheet by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, explores traditional and nontraditional opportunities for generating income in the interface. Includes references. Published by the UF School of Forest Resources and Conservation, August 2008.